Emergency management of dental trauma: a survey of public knowledge, awareness, and attitudes in Al-Madinah Al-Munawwarah - Nourwali IM; Maddhar AK; Alsaati BH; Alhazmi RA; AlAyoubi SM; AlHarbi SS (Dove Medical Press, 2019)
Ibrahim Mohammedali Nourwali,1 Abdulrahman Khaleel Maddhar,2 Bayan Hussain Alsaati,3 Rahaf Abed Alhazmi,2 Shahad Mohammed AlAyoubi,2 Shaima Sabri AlHarbi31Oral & Maxillofacial Surgery, Faculty of Dentistry, Taibah University, Medina, Saudi Arabia; 2Faculty of Dentistry, Taibah University, Medina, Saudi Arabia; 3Faculty of Dentistry, Taibah University, Medina, Saudi ArabiaCorrespondence: Shaima Sabri AlHarbiFaculty of Dentistry, Taibah University, 3587 Hassan Ibn Thabit Street-Al Iskan, Medina 42317-7279, Saudi ArabiaTel +966 55 187 9359Email shimasabria@gmail.comBackground: Dental trauma is one of the most commonly encountered dental emergencies. The prognosis is determined by the appropriate intervention and immediate management of the traumatized teeth. Thus, public awareness is a leading determinant of treatment success. The purpose of this study was to assess the knowledge, attitudes, and awareness of Al-Madinah Al-Munawwarah residents regarding the management of dental trauma.Methods: This cross-sectional observational study was conducted between December 2016 and January 2018. A two-part self-administered questionnaire comprising 13 closed-ended questions was used. Part one contained questions to elicit demographic data that included information related to the participants’ sources of dental trauma. Part two assessed their knowledge and attitudes regarding the most common types of dental trauma. The data were analyzed with IBM SPSS Statistics for Windows, Version 22.0 software.Results: A total of 598 participants were included in this study. The results indicated that 64% of the participants knew where to go to receive treatment for dental trauma, and 74% were aware of the differences in the management of the primary and permanent teeth after trauma. A majority (83%) did not have any information about these issues; however, 83% were interested in learning about the appropriate management of dental trauma.Conclusion: The study participants were found to have low levels of knowledge. A majority had never received information about the management of dental trauma or avulsed teeth. Education programs are necessary for promoting positive attitudes by increasing the knowledge about dental trauma management.Keywords: avulsion, dental trauma, awareness, knowledge, management